2011
DOI: 10.1111/j.1439-0310.2011.01957.x
|View full text |Cite
|
Sign up to set email alerts
|

Signalling and Sexual Conflict: Female Spiders Use Stridulation to Inform Males of Sexual Receptivity

Abstract: The use of acoustic signals by males during courtship and mating is well known. Nevertheless, their association with female unwillingness to mate is much less studied. In spiders, stridulation during sexual interactions is relatively common in some groups, but mainly restricted to males. In the pholcid spider Holocnemus pluchei, both sexes have stridulatory organs. The aims of the present work were (1) to establish whether female stridulation occurs during intra‐ and inter‐sexual interactions, (2) to determine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 40 publications
(64 reference statements)
0
24
0
Order By: Relevance
“…These females thus appear to give males an early indication of their forthcoming decision. An analogous notice has been observed for female stridulation in some pholcid spiders, including the above P. globosus, in which females stridulate when an encounter is less likely to lead to copulation (Peretti et al 2006;Dutto et al 2011). I suspect that this type of feedback, before and during copulation, may turn out to be widespread (see e.g., Baena and Eberhard 2007).…”
Section: Females Warn Males Of Likely Failurementioning
confidence: 62%
“…These females thus appear to give males an early indication of their forthcoming decision. An analogous notice has been observed for female stridulation in some pholcid spiders, including the above P. globosus, in which females stridulate when an encounter is less likely to lead to copulation (Peretti et al 2006;Dutto et al 2011). I suspect that this type of feedback, before and during copulation, may turn out to be widespread (see e.g., Baena and Eberhard 2007).…”
Section: Females Warn Males Of Likely Failurementioning
confidence: 62%
“…In contrast, his observations of female stridulatory behavior suggest a defensive or even aggressive function, because females that readily accepted the male never rub their pedipalps against the chelicerae, while females that seemed less sexually receptive often rub the pedipalps against the chelicerae (Huber 1995). In H. pluchei, female stridulation occurs during courtship but never during copulation (Dutto et al 2011;Huber 1995). Therefore, stridulation by females conveys a negative message both in intrasexual and in intersexual contexts (Dutto et al 2011).…”
Section: Female Copulatory Behavior: Resistance Versus Copulatory Diamentioning
confidence: 84%
“…In H. pluchei, female stridulation occurs during courtship but never during copulation (Dutto et al 2011;Huber 1995). Therefore, stridulation by females conveys a negative message both in intrasexual and in intersexual contexts (Dutto et al 2011). The strength of the "negative" message seems to be defined by the intensity of stridulation.…”
Section: Female Copulatory Behavior: Resistance Versus Copulatory Diamentioning
confidence: 97%
See 1 more Smart Citation
“…For example, Dutto et al (2011) showed that once-mated females of H. pluchei altered their stridulatory behaviour based on male courtship tactics. For example, Dutto et al (2011) showed that once-mated females of H. pluchei altered their stridulatory behaviour based on male courtship tactics.…”
Section: Discussionmentioning
confidence: 99%